The relationship between social support and psychological well-being of college students during Covid-19 pandemic - Alza, Nadatuljannah; Armalita, Rani; Puspasari, Dwi (International Journal of Research in Counseling and Education, 2021)
One of those affected by the COVID-19 pandemic is college students. It made the learning process that was previously carried out face-to-face became online. This condition affects the psychological well-being of college students. One of the factors that influence psychological well-being is social support. The goal of this research is to investigate the relationship between social support and the psychological well-being of college students during the COVID-19 pandemic. The method used in this research was a quantitative method with a correlational design. A total of 351 college students who attend lectures during the COVID-19 pandemic and studied in the city of Padang, West Sumatra, Indonesia became a subject of this research. Measurement was carried out by adapting the scale and each scale has a reliability of .795 and .894. The results showed that social support was significantly related to the psychological well-being of college students during the COVID-19 pandemic which could be seen from the significance value of .00 (p<.05). The Pearson correlation value in the research was .668, this indicates that the relationship between social support and the psychological well-being of college students during the COVID-19 pandemic is in a strong category.